Process optimization and feature analysis of an anaerobic fermentation microbial community in a cold region. Issue 1 (31st December 2022) - Lu, Binyu; Jia, Meiyu; Pei, Zhanjiang; Shi, Fengmei; Gao, Yabing; Liu, Jie
ABSTRACT: Anaerobic digestion can be inhibited at low temperatures in cold regions. This study investigated the effects of fermentation temperature, total solids (TS) concentration and stirring speed on swine manure biogas production by anaerobic fermentation experiments based on the quadratic regression orthogonal rotation combination method. The results showed that the fermentation temperature and TS had significant effects on swine manure biogas production rates.   The theoretical and experimental amounts of gas production at the optimal process parameters were 2857.46 mL and 2820.0 mL, respectively. Methanobacteria and Methanomicrobia were the main methane-producing genera for samples in six different anaerobic digestion phases, with relative abundances of 2.25 to 5.59% and 0.85 to 3.02%, respectively. The acetotrophic bacterium Methanosaeta was absolutely dominant, attributable to acetic acid metabolic pathways occurring more easily at low temperatures and Methanosaeta was more competitive when the acetic acid concentration was in the range of 38.8 to 252.2 mg L −1 .